A randomized controlled evaluation of an educational resource to address fertility concerns after cancer. Issue 9 (21st April 2021) - Ussher, Jane M; Perz, Janette; Hawkey, Alexandra J
Abstract: Objective: This study evaluated the acceptability and impact of a written oncofertility educational resource (ER), as a self‐help intervention (SH), and as an adjunct to a one‐hour health‐care professional discussion (HP). Methods: Within a randomized control trial (RCT), 194 adults with cancer (175 womens; 19 mens) were allocated to the SH or HP intervention. 127 completed 6‐weeks post‐intervention measures, a retention rate of 65.85%. Results: Across interventions, the ER was rated as highly acceptable and useful, in terms of ease of understanding, and information. Heath literacy significantly increased post‐intervention, including functional literacy, communicative literacy, and critical health literacy. There were no significant changes in ratings of fertility distress or general distress pre‐post intervention. Quality of life was significantly reduced post intervention. Those in the HP condition reported higher quality of life and greater likelihood of communication with others about fertility, most notably with intimate partners, post‐intervention. Qualitative identification of increased knowledge, confidence with communication and normalization of fertility concerns, reflects increased health literacy, and provides explanation for significant reductions in feeling nervous and fearful about fertility treatments post‐intervention. Conclusions: Our findings confirm the importance of information provision about the impact of cancer on fertility. Written ERs are a useful adjunct to a patient‐clinician discussion, increasing health literacy, which facilitates knowledge, self‐efficacy and management of fertility concerns and changes.